Pengaruh Harga Emas Dan Nilai Tukar Rupiah Dolar Di Indonesia Terhadap Indeks Harga Saham Gabungan (ihsg) 2020 - 2022 - Zulkarnaen, Fadillah Hafizh; Santoso, Teguh Iman (eProceedings of Management, 2024)
Entering 2020, the global economy is facing great pressure due to the COVID-19 pandemic, which has causedinstability in various countries. The impact can be seen on capital markets and currency exchange rates. Fluctuationsin the "Composite Stock Price Index" (IHSG) in Indonesia reflect volatility in the money market and capital market,the decline in the value of the rupiah against the US dollar, and changes in global gold prices. Gold prices werehighest in August 2020 and lowest in January 2020, while the rupiah exchange rate reached its peak in April 2020and fell in January 2020. JCI showed recovery, reaching its peak in April 2022 after a sharp decline in March 2020.This research examines how the JCI is influenced by gold prices and currency exchange rates between 2020 and 2022.These findings highlight the complexity and interconnectivity between global commodity markets, exchange rates, andthe performance of the Indonesian capital market. This research provides insight for investors, policy makers andacademics in understanding the factors that influence the JCI, especially in the context of global economic shockssuch as the COVID-19 pandemic. Secondary data was taken from Bank Indonesia and Investing.com reports for 2020-2022, analyzing world gold prices, the rupiah exchange rate against the dollar, and the IHSG. Analysis shows thatthe JCI is not significantly influenced by the exchange rate or gold price. Keywords-Composite Stock Price Index (IHSG); gold price, rupiah exchange rate.